Shock-resistant protective water-based paint for helmet
By using components such as epoxy resin and water-based polyurethane to construct interpenetrating polymer networks and nanostructures in anti-impact protection water-based coatings with helmets, the shortcomings in hardness, wear resistance and durability of existing water-based coatings are solved, and higher protective performance and service life are achieved.
Patent Information
- Application Number
- CN202411866203.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing water-based coatings have insufficient hardness and wear resistance in the anti-impact protection of helmets, making it difficult to effectively absorb and disperse energy, resulting in a reduced protective effect and poor durability in complex environments.
A helmet anti-impact protection water-based coating is adopted, and the composition includes epoxy resin, water-based polyurethane, chitosan, polystyrene microspheres, nanoclay, acrylic resin, silica and titanium dioxide, etc. By building interpenetrating polymer networks and nanostructures, the flexibility, antibacteriality, impact resistance and self-cleaning ability of the coating are enhanced.
It significantly improves the overall performance of the paint, allowing it to provide more effective protection in helmet applications, extends service life, and maintains good performance in complex environments.
Smart Images

Figure BDA0005194399100000291 
Figure BDA0005194399100000301 
Figure HDA0005194399110000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-based coatings, and in particular to an anti-impact protective water-based coating for helmets. Background Art
[0002] With the improvement of modern safety awareness, helmets, as important equipment to protect the head from impact damage, have been widely used in military, industrial, sports and other fields. The protective performance of a helmet depends largely on the properties of its surface coating. Traditional helmet coatings often focus on improving a single function, such as hardness, wear resistance or corrosion resistance, while ignoring the comprehensive performance of the coating in complex and changing environments. Especially when subjected to high-speed impact, traditional coatings may crack or peel off due to lack of sufficient toughness and energy absorption capacity, thus failing to provide effective protection for the wearer.
[0003] In recent years, water-based paint has gradually become a research hotspot in the paint industry due to its advantages such as environmental protection, low toxicity, and easy construction. However, existing water-based paints still have many shortcomings when used for helmet impact protection. For example, although some water-based paints have high hardness and wear resistance, they are difficult to effectively absorb and disperse energy when impacted, resulting in a significant reduction in the protective effect of the coating. In addition, some water-based paints have poor durability in complex environments and are prone to aging, fading, or performance degradation after long-term use.
[0004] Therefore, we propose a helmet anti-impact protective water-based coating to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an anti-impact protective water-based paint for helmets.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses an anti-impact protective water-based paint for helmets, comprising the following components in parts by weight: 20-30 parts of epoxy resin, 20-30 parts of water-based polyurethane, 5-10 parts of chitosan, 5-10 parts of polystyrene microspheres, 3-5 parts of nano clay, 10-15 parts of acrylic resin, 3-5 parts of silicon dioxide, 2-3 parts of titanium dioxide, 0.5-1 part of defoaming agent and 0.5-1 part of antifoaming agent.
[0008] As the preferred technical solution:
[0009] The above-mentioned water-based helmet impact protection coating comprises the following components in parts by weight: 23 parts of epoxy resin, 26 parts of water-based polyurethane, 7 parts of chitosan, 8 parts of polystyrene microspheres, 4 parts of nanoclay, 12 parts of acrylic resin, 4 parts of silicon dioxide, 2 parts of titanium dioxide, 0.8 parts of defoaming agent, and 0.7 parts of antifoaming agent.
[0010] The invention relates to a water-based helmet impact protection coating as described above, wherein the epoxy resin is one of epoxy resin e-44 and epoxy resin e-51, and the viscosity of the epoxy resin is 1000-1500 mPa·s; the water-based polyurethane adopts anionic water-based polyurethane, and the average particle size is 50-100 nanometers; the molecular weight of the chitosan is 100,000-300,000; the average particle size of the polystyrene microspheres is 1-5 micrometers; the glass transition temperature of the acrylic resin is 30-50°C, and the weight-average molecular weight is 50,000-100,000; the crystal form of the titanium dioxide is one of rutile type or anatase type, and the average particle size is 0.2-0.4 micrometer; the defoamer is one of dimethyl silicone oil and polyether; the antifoaming agent is one of hydrophobic silica and fatty alcohol.
[0011] In the above-mentioned water-based anti-impact protective coating for helmets, the chitosan and the water-based polyurethane construct an interpenetrating polymer network, wherein the chitosan network provides biocompatibility and antibacterial functions, while the water-based polyurethane network contributes flexibility and wear resistance; the polystyrene microspheres are elastomers with a deformable core, which is composed of a cross-linked polymer network and can change shape and absorb energy under the action of external forces. The surface of the polystyrene microspheres is covered with a nanoscale self-healing layer, which can quickly self-repair when the microspheres are broken to maintain the integrity of the coating.
[0012] In the above-mentioned water-based helmet impact protection coating, the chitosan is modified and functional groups with the ability to chelate calcium ions are introduced into its molecular chain; the acrylic resin is a copolymer with a core-shell structure, the core layer is a hard segment, which provides hardness and wear resistance to the coating, and the shell layer is a soft segment, which gives the coating flexibility and impact resistance; the water-based polyurethane is a star-shaped structure, the central core is a rigid aromatic structure, which provides high strength and wear resistance, and the periphery is a flexible aliphatic chain segment, which gives the coating excellent elasticity and cold resistance; the surface of the titanium dioxide nanoparticles is modified with a layer of metal oxide film with photocatalytic activity by atomic layer deposition technology, and is designed into a nano-shaped structure, including nanoflowers, nanotrees or nanostars; the interior of the polystyrene microspheres is a core-shell structure with a gradient density distribution, and / or the surface of the polystyrene microspheres is modified with nano-scale silica particles.
[0013] The above-mentioned water-based helmet impact protection coating is a core-shell structure nanoparticle constructed by using the silicon dioxide as the core and the titanium dioxide as the shell. This structure can combine the hardness of silicon dioxide and the photocatalytic performance of titanium dioxide to enhance the self-cleaning ability of the coating. The self-cleaning ability index is set as SCI, then:
[0014] SC I=\frac{k\t imesA surface}{M particle}
[0015] Where: k is the photocatalytic degradation rate constant; A surface is the surface area of nanoparticles per unit mass of coating, obtained by BET specific surface area test; M particle is the mass of the nanoparticle;
[0016] k=-\frac{\ln(C / C_0)}{t}
[0017] Where: C is the concentration of the target pollutant after the reaction; C_0 is the initial concentration of the target pollutant before the reaction; t is the photocatalytic reaction time.
[0018] The second aspect of the present invention provides a method for preparing a water-based helmet impact protection coating, comprising the following steps:
[0019] S1: Using ultrasonic-assisted high-speed stirring technology, water-based polyurethane and chitosan solution are mixed to form a composite emulsion;
[0020] S2: dispersing nanoclay in deionized water to form a stable suspension, and slowly adding acrylic resin under stirring to form a dense pre-coating emulsion;
[0021] S3: mixing the preheated epoxy resin with a diluent to reduce the viscosity, gradually adding silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed to obtain an epoxy resin base system;
[0022] S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the mixed emulsion, and a defoamer and an antifoaming agent are added at the same time, and the stirring is continued until all components are completely blended to form a uniform and stable coating system;
[0023] S5: The polystyrene microspheres are dispersed, and then slowly added into the coating system in S4 under continuous stirring, and stirring is continued for a period of time to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
[0024] As the preferred technical solution:
[0025] In the method for preparing the water-based helmet impact protection coating as described above, in S2, a layer-by-layer assembly technique is used to adsorb acrylic resin molecules layer by layer on the surface of nanoclay to construct a pre-coating emulsion with a multi-layer structure.
[0026] The method for preparing the water-based anti-impact protective coating for helmets as described above, wherein S4 specifically comprises:
[0027] S41: Under controlled stirring speed, the composite emulsion and the pre-coating emulsion are first pre-mixed, and a variable speed stirring technology is used, the initial stirring speed is set to 400 rpm, and the stirring speed is gradually increased to 900 rpm;
[0028] S42: while premixing, preparing a dynamic mixer, which has a rotating element inside and can generate strong shear force and impact force while controlling the stirring speed, and preheating the dynamic mixer to reduce the influence of temperature difference on the mixing process;
[0029] S43: slowly adding the preheated epoxy resin base system into the dynamic mixer, and while adding the epoxy resin base system, a strong shear force and impact force are generated by the rotating element of the dynamic mixer;
[0030] S44: During the mixing process, when the amount of epoxy resin base system added reaches 50% of the total amount, the defoamer and the antifoam agent are slowly added;
[0031] S45: During the entire mixing process, the viscosity, temperature and bubble conditions of the mixed system are continuously monitored, and the continuous stirring time is adjusted according to the monitoring results;
[0032] S46: When all components are completely blended, stop stirring and perform post-processing on the mixed coating system to ensure the purity and coating effect of the coating.
[0033] The method for preparing the water-based anti-impact protective coating for helmets as described above, wherein S5 specifically comprises the following steps:
[0034] S51: placing polystyrene microspheres in a solvent containing a dispersant, using a high-speed disperser for preliminary dispersion, placing the polystyrene microsphere suspension after preliminary dispersion in an ultrasonic processor, and using an optical microscope to evaluate the particle size distribution and dispersion state of the dispersed polystyrene microspheres to ensure that the microspheres achieve the desired uniform dispersion effect;
[0035] S52: before adding the polystyrene microspheres, pre-stirring the coating system obtained in step S4, and gradually adding the dispersed polystyrene microsphere suspension into the coating system by slowly pumping under continuous stirring;
[0036] S53: After all the polystyrene microspheres are added, gradually increase the stirring speed and evaluate the stability of the coating system after stirring, including standing and observing whether stratification, precipitation or phase separation occurs, and measuring the rheological properties of the coating by a rheometer. If the stability of the coating system is good, post-processing is carried out, followed by sealed packaging to obtain the final helmet impact protection water-based coating product.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] Chitosan and waterborne polyurethane construct an interpenetrating polymer network, which not only combines the biocompatibility and antibacterial properties of chitosan, but also utilizes the flexibility of waterborne polyurethane, thereby giving it antibacterial function while maintaining the flexibility of the coating. The formation of this network structure greatly enhances the comprehensive performance of the coating, making it more suitable for application scenarios such as helmets that need to meet both protection and hygiene requirements;
[0039] Polystyrene microspheres have a deformable core that can change shape and absorb energy under external force, effectively dispersing impact stress and improving the impact resistance of the coating. Epoxy resin and waterborne polyurethane, as the main resins of the coating, jointly provide high strength and toughness, further enhancing the impact resistance of the coating. The addition of nanoclay, through its lamellar structure, effectively prevents the expansion of cracks and improves the crack resistance of the coating;
[0040] Modified chitosan can chelate calcium ions and shrink or stretch according to changes in the concentration of calcium ions in the environment, giving the coating adaptability and intelligent responsiveness, allowing the coating to automatically adjust its performance according to different usage conditions. The waterborne polyurethane network contributes flexibility and wear resistance, and combined with the rigid structure of epoxy resin, a rigid and flexible coating system is formed. The core-shell structure of acrylic resin, the core layer provides hardness, and the shell layer provides flexibility and impact resistance, further improving the overall performance of the coating;
[0041] The surface of titanium dioxide nanoparticles is modified with a photocatalytically active metal oxide film and designed into a nano-shaped structure, which enhances the photocatalytic performance of the particles and makes the coating have excellent light scattering, light absorption and light conversion properties. By constructing silicon dioxide-titanium dioxide core-shell structure nanoparticles, the hardness of silicon dioxide and the photocatalytic performance of titanium dioxide are combined, which significantly enhances the self-cleaning ability of the coating;
[0042] The high specific surface area and thickening effect of nanoclay combined with the film-forming and water-resistant properties of acrylic resin form a dense waterproof coating that effectively resists the penetration of water and moisture. This improved waterproof performance complements the impact resistance of polystyrene microspheres, and together they enhance the stability and durability of the coating in various environments.
[0043] In summary, in the present invention, by adding components such as polystyrene microspheres and nanoclay, the coating can absorb and disperse external impact forces, effectively protecting the internal structure of the helmet from damage; the synergistic effect of water-based polyurethane and acrylic resin makes the coating have both excellent wear resistance and good flexibility, thereby extending the service life of the helmet; the modified chitosan can give the coating self-adaptation and intelligent responsiveness, so that it can maintain good performance in different environments; by constructing titanium dioxide nanoparticles with photocatalytic activity, the coating has self-cleaning ability and can effectively degrade organic pollutants attached to the surface; the use of a water-based system is more environmentally friendly and harmless to human health compared to traditional oil-based coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a transmission electron microscope photograph of the microspheres in Example 4 of the present invention;
[0045] Figure 2 The data curves of the embodiments, control examples and comparative examples of the present invention are shown in FIG. Figure 1 ;
[0046] Figure 3 The data curves of the embodiments, control examples and comparative examples of the present invention are shown in FIG. Figure 2 ;
[0047] Figure 4 The data curves of the embodiments, control examples and comparative examples of the present invention are shown in FIG. Figure 3 ;
[0048] Figure 5 The data curves of the embodiments, control examples and comparative examples of the present invention are shown in FIG. Figure 4 . DETAILED DESCRIPTION
[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0050] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0051] The invention discloses an anti-impact protective water-based paint for helmets, comprising the following components in parts by weight: 20-30 parts of epoxy resin, 20-30 parts of water-based polyurethane, 5-10 parts of chitosan, 5-10 parts of polystyrene microspheres, 3-5 parts of nano clay, 10-15 parts of acrylic resin, 3-5 parts of silicon dioxide, 2-3 parts of titanium dioxide, 0.5-1 part of defoaming agent and 0.5-1 part of antifoaming agent.
[0052] Among them, the epoxy resin is one of epoxy resin e-44 or epoxy resin e-51, and the viscosity of the epoxy resin is 1000-1500mPa·s; the waterborne polyurethane adopts anionic waterborne polyurethane, and the average particle size is 50-100 nanometers; the molecular weight of chitosan is 100,000-300,000; the average particle size of polystyrene microspheres is 1-5 microns; the glass transition temperature of acrylic resin is 30-50°C, and the weight average molecular weight is 50,000-100,000; the crystal form of titanium dioxide is one of rutile type or anatase type, and the average particle size is 0.2-0.4 microns; the defoamer is one of dimethyl silicone oil and polyether; the antifoaming agent is one of hydrophobic silica and fatty alcohol.
[0053] Anionic waterborne polyurethane and chitosan are used to form an interpenetrating structure. In the waterborne coating for helmet impact protection, chitosan, as a natural polymer compound, has good biocompatibility and is non-toxic to human tissues, organs and cells. Combining it with anionic waterborne polyurethane to form an interpenetrating structure can significantly improve the biosafety of the coating and reduce the risk of allergic reactions or toxicity that may be caused during use.
[0054] Chitosan has special antibacterial and anti-inflammatory functions, which are effectively retained in the coating. Through the interpenetrating structure with waterborne polyurethane, the coating not only has flexibility, but also integrates the antibacterial properties of chitosan, thus providing an additional layer of hygienic protection in helmet applications, reducing the possibility of bacterial growth and spread.
[0055] Anionic waterborne polyurethane is known for its excellent flexibility and wear resistance. This flexibility and wear resistance are further enhanced by forming an interpenetrating structure with chitosan. The coating can absorb and disperse energy more effectively when impacted, reducing direct damage to the head while maintaining the integrity and protective properties of the coating.
[0056] The formation of an interpenetrating polymer network structure allows chitosan and waterborne polyurethane to form a tight bond. This network structure not only enhances the stability of the coating, but also improves the adhesion between the coating and the helmet substrate. During long-term use, the coating can maintain stable performance and is not prone to peeling, cracking or performance degradation.
[0057] It should be noted that chitosan and waterborne polyurethane construct an interpenetrating polymer network, in which the chitosan network provides biocompatibility and antibacterial functions, while the waterborne polyurethane network contributes flexibility and wear resistance; polystyrene microspheres are elastomers with a deformable core, which is composed of a cross-linked polymer network. It can change its shape and absorb energy under the action of external force. The surface of the polystyrene microspheres is covered with a nanoscale self-healing layer, which can quickly self-repair when the microspheres are broken to maintain the integrity of the coating.
[0058] In order to specifically realize the construction of an interpenetrating polymer network of chitosan and waterborne polyurethane in a helmet anti-impact protective waterborne coating, and the introduction of polystyrene microspheres with a specific structure to enhance the impact resistance, an embodiment is given below:
[0059] 1. Construction of interpenetrating polymer networks
[0060] Raw material selection and ratio:
[0061] Waterborne polyurethane: Choose a waterborne polyurethane dispersion with excellent flexibility and wear resistance, such as a waterborne polyurethane synthesized based on polyether diol and toluene diisocyanate (TDI), with a solid content of 30%. Chitosan: Choose chitosan powder with a deacetylation degree higher than 90%, which has good biocompatibility and antibacterial properties. The mass ratio of chitosan to waterborne polyurethane is 1:3 to ensure that the two can form a good interpenetrating polymer network.
[0062] Preparation of interpenetrating polymer network: Dissolve chitosan powder in acetic acid solution to prepare chitosan acetic acid solution. Mix the aqueous polyurethane dispersion and chitosan acetic acid solution in the above proportions, and add appropriate amounts of crosslinking agent (such as diisocyanate) and catalyst. Heat the mixture to an appropriate temperature (such as 60-80°C) under stirring conditions and react for several hours until a stable interpenetrating polymer network structure is formed.
[0063] Performance characterization: Characterize the structure of the interpenetrating polymer network by infrared spectroscopy (IR) and scanning electron microscopy (SEM). Test the biocompatibility and antibacterial properties of the coating to ensure the effective function of the chitosan network. Test the flexibility and wear resistance of the coating to verify the contribution of the waterborne polyurethane network.
[0064] 2. Preparation and characteristics of polystyrene microspheres
[0065] Raw material selection and ratio: Cross-linking agent: such as divinylbenzene (DVB), used to construct the deformable core of polystyrene microspheres. Styrene monomer: as the main component of polystyrene microspheres. Initiator: such as azobisisobutyronitrile (AI BN), used to initiate the polymerization reaction.
[0066] Preparation of polystyrene microspheres: Styrene monomer, crosslinker and initiator are mixed in a certain proportion, and an appropriate amount of dispersant (such as polyvinyl pyrrolidone, PVP) is added to maintain the stability of the microspheres. The mixture is heated to an appropriate temperature (such as 70-80°C) under stirring conditions and reacted for several hours until a stable polystyrene microsphere emulsion is formed. Polystyrene microspheres with a deformable core are obtained through steps such as centrifugation, washing and drying.
[0067] Covering of self-healing layer: Disperse polystyrene microspheres in a solution containing nano-scale self-healing materials (such as a mixed solution containing nano-silicon dioxide and self-healing polymers). Use physical or chemical methods (such as electrostatic adsorption, chemical bonding, etc.) to evenly cover the surface of the polystyrene microspheres with the self-healing layer.
[0068] Performance characterization: The morphology of polystyrene microspheres and the coverage of the self-healing layer were observed by SEM and transmission electron microscopy (TEM). The deformability and energy absorption capacity of the microspheres under external forces were verified by compression tests and impact tests. The rupture of the microspheres was simulated to observe and record the effect and repair speed of the self-healing layer.
[0069] Specific data example: The solid content of waterborne polyurethane is 30%. The mass ratio of chitosan to waterborne polyurethane is 1:3. The amount of crosslinking agent divinylbenzene is 5% of the mass of styrene monomer. The amount of initiator azobisisobutyronitrile is 0.5% of the mass of styrene monomer. The average diameter of polystyrene microspheres is 5 microns. The thickness of the self-healing layer is nanometer-level, and the specific value can be determined by TEM measurement.
[0070] It should be noted that chitosan has been modified and functional groups with the ability to chelate calcium ions have been introduced into its molecular chain. In a solution containing calcium ions, chitosan molecules can "absorb calcium ions" and shrink, and in a solution with the ability to chelate calcium ions, they "lose calcium ions" and stretch, giving the coating adaptability and intelligent responsiveness; acrylic resin is a copolymer with a core-shell structure, the core layer is a hard segment, which provides hardness and wear resistance for the coating; the shell layer is a soft segment, which gives the coating flexibility and impact resistance; waterborne polyurethane is a star-shaped structure, the central core is a rigid aromatic structure, which provides high strength and wear resistance; and the periphery is a flexible aliphatic chain segment, which gives the coating excellent elasticity and cold resistance. properties; the surface of titanium dioxide nanoparticles is modified with a layer of metal oxide film with photocatalytic activity by atomic layer deposition technology, and is designed into nano-shaped structures, including nanoflowers, nanotrees or nanostars; these structures not only enhance the photocatalytic performance of the particles, but also make the coating have excellent light scattering, light absorption and light conversion properties; the interior of the polystyrene microspheres is a core-shell structure with a gradient density distribution, the core part has a high density and high hardness, which is used to improve the impact resistance of the coating; while the outer shell part has a low density and good elasticity, which is used to improve the touch and wear resistance of the coating; and / or the surface of the polystyrene microspheres is modified with nano-scale silica particles to further enhance the hardness and scratch resistance of the coating.
[0071] In the water-based coating for helmet impact protection, it is necessary to achieve the modification of chitosan, the core-shell structure design of acrylic resin, the star structure of waterborne polyurethane, the surface modification of titanium dioxide nanoparticles, and the gradient density core-shell structure and surface modification of polystyrene microspheres. The following are examples:
[0072] 1. Modification of chitosan
[0073] Raw material selection and ratio: Chitosan: chitosan powder with a deacetylation degree of more than 90% is selected. Modifier: functional groups containing calcium ion chelating ability (such as ethylenediaminetetraacetic acid, EDTA) or its derivatives. The mass ratio of chitosan to modifier is 10:1.
[0074] Modification treatment steps: Dissolve chitosan powder in 1% acetic acid solution to prepare chitosan solution. Dissolve the modifier in an appropriate amount of solvent, and then slowly add it to the chitosan solution while stirring. React at room temperature for 24 hours to allow the modifier to be fully grafted onto the molecular chain of chitosan. After the reaction is completed, precipitate the modified chitosan with ethanol and wash it several times with deionized water to remove unreacted modifier and impurities. Finally, dry the modified chitosan to constant weight to obtain chitosan with the ability to chelate calcium ions.
[0075] Performance verification: The structure of the modified chitosan was characterized by infrared spectroscopy (IR) and nuclear magnetic resonance hydrogen spectrum (^1H-NMR) to confirm the successful grafting of functional groups. The modified chitosan was dispersed in a solution containing calcium ions to observe its shrinkage after absorbing calcium ions. The shrunk chitosan was dispersed in a solution with the ability to chelate calcium ions to observe its elongation after losing calcium ions.
[0076] 2. Core-shell structure design of acrylic resin
[0077] Raw material selection and ratio: Hard segment monomer: methyl methacrylate (MMA), providing hardness and wear resistance. Soft segment monomer: butyl acrylate (BA), giving flexibility and impact resistance. Initiator: azobisisobutyronitrile (AI BN). The mass ratio of hard segment to soft segment monomer is 7:3.
[0078] Core-shell structure preparation steps:
[0079] In a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, add an appropriate amount of solvent and hard segment monomer MMA, as well as initiator AI BN. Heat to 75°C to start the polymerization reaction to form a hard segment core. When the hard segment core reaches a certain size, start to drop the soft segment monomer BA and continue to react at the same temperature so that the soft segment forms a shell on the surface of the hard segment core. After the reaction is completed, ethanol is used to precipitate the core-shell structure of the acrylic resin, and it is washed several times with deionized water to remove unreacted monomers and impurities. Finally, the acrylic resin is dried to constant weight.
[0080] Performance verification: Observe the core-shell structure of acrylic resin by transmission electron microscopy (TEM). Test the hardness and wear resistance of the coating to verify the contribution of the hard segment core. Test the flexibility and impact resistance of the coating to verify the contribution of the soft segment shell.
[0081] 3. Star structure design of waterborne polyurethane
[0082] Raw material selection and ratio: Rigid aromatic diisocyanates: such as toluene diisocyanate (TDI), provide high strength and wear resistance. Flexible aliphatic diols: such as polyethylene glycol (PEG), impart excellent elasticity and cold resistance. Trifunctional alcohols: as the central core of the star structure, such as glycerol or pentaerythritol.
[0083] Preparation steps of star structure: add trifunctional alcohol and appropriate amount of solvent into a three-necked flask and heat to an appropriate temperature. Slowly add rigid aromatic diisocyanate while stirring, so that the trifunctional alcohol and diisocyanate react to form a central core of the star structure. Subsequently, add flexible aliphatic diol and continue the reaction to connect the flexible chain segments to the central core to form a waterborne polyurethane with a star structure. After the reaction is completed, wash with deionized water several times to remove unreacted raw materials and impurities. Finally, dry the waterborne polyurethane to constant weight and disperse it in water to form an aqueous dispersion.
[0084] Performance verification: Characterize the star structure of waterborne polyurethane by gel permeation chromatography (GPC) and nuclear magnetic resonance hydrogen spectrum (^1H-NMR). Test the tensile strength and wear resistance of the coating to verify the contribution of the rigid aromatic structure. Test the elasticity and cold resistance of the coating to verify the contribution of the flexible aliphatic segment.
[0085] 4. Surface modification of titanium dioxide nanoparticles
[0086] Raw material selection and ratio: Titanium dioxide nanoparticles: Anatase titanium dioxide with a particle size of 20 nanometers is selected. Metal oxide precursor: such as tetrabutyl titanate, used to deposit metal oxide films with photocatalytic activity. Solvent: ethanol or isopropanol.
[0087] Surface modification step: Disperse titanium dioxide nanoparticles in a solvent to form a stable suspension. Dissolve the metal oxide precursor in another solvent, and then slowly drop it into the titanium dioxide suspension while stirring. React at room temperature for 24 hours to allow the metal oxide precursor to hydrolyze and condense into a film on the surface of the titanium dioxide nanoparticles. Through the steps of centrifugation, washing and drying, titanium dioxide nanoparticles with a metal oxide film on the surface are obtained.
[0088] Nano-shape structure design: The surface-modified titanium dioxide nanoparticles are synthesized in a controlled manner under high temperature and high pressure using a hydrothermal method or a solvothermal method to form structures such as nanoflowers, nanotrees or nanostars.
[0089] Performance verification: The shape and surface modification of titanium dioxide nanoparticles were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The photocatalytic performance, light scattering performance, light absorption performance and light conversion performance of the coating were tested.
[0090] 5. Gradient density core-shell structure and surface modification of polystyrene microspheres
[0091] Raw material selection and ratio: Polystyrene monomer: styrene (St). Initiator: azobisisobutyronitrile (AI BN). Density regulator: such as high-density inorganic nanoparticles (such as silicon dioxide) and low-density organic matter (such as polyethylene glycol). Surface modifier: nano-scale silicon dioxide particles.
[0092] Preparation steps of gradient density core-shell structure: Add appropriate amount of solvent and polystyrene monomer, as well as initiator AI BN, to a three-necked flask equipped with a stirrer, thermometer and reflux condenser. Heat to 70°C to start the polymerization reaction. At the beginning of the reaction, high-density inorganic nanoparticles are added as the core part to make the core part high in density and hardness. As the reaction proceeds, low-density organic matter is gradually added as the shell part to make the shell part low in density and good in elasticity. After the reaction is completed, polystyrene microspheres with gradient density core-shell structure are precipitated with ethanol and washed several times with deionized water.
[0093] Surface modification step: The precipitated polystyrene microspheres are dispersed in an appropriate amount of solvent to form a stable suspension. Nano-scale silica particles are dispersed in another solvent, and then slowly added to the polystyrene microsphere suspension while stirring. The reaction is allowed to proceed at room temperature for a period of time, so that the silica particles are uniformly adsorbed on the surface of the polystyrene microspheres. Through the steps of centrifugation, washing and drying, polystyrene microspheres with surface modified with nano-scale silica particles are obtained.
[0094] Performance verification: Observe the gradient density core-shell structure and surface modification of polystyrene microspheres by scanning electron microscopy (SEM). Test the impact resistance, touch and wear resistance of the coating. Test the hardness and scratch resistance of the coating.
[0095] Specific data examples: The mass ratio of chitosan to modifier is 10:1. The mass ratio of hard segment to soft segment monomer in acrylic resin is 7:3. The molar ratio of rigid aromatic diisocyanate to flexible aliphatic diol in waterborne polyurethane is 1:3. The particle size of titanium dioxide nanoparticles is 20 nanometers. The average diameter of polystyrene microspheres is 5 microns. The particle size of surface-modified nano-scale silica particles is 10 nanometers.
[0096] It should be noted that the core-shell structure nanoparticles are constructed based on silicon dioxide as the core and titanium dioxide as the shell. This structure can combine the hardness of silicon dioxide and the photocatalytic performance of titanium dioxide to enhance the self-cleaning ability and durability of the coating. The self-cleaning ability index is set as SCI, then: SCI = \frac{k\t imesA surface}{M particle};
[0097] Where: k is the photocatalytic degradation rate constant; A surface is the surface area of nanoparticles per unit mass of coating, obtained by BET specific surface area test; M particle is the mass of the nanoparticle;
[0098] k = -\frac{\ln(C / C_0)}{t};
[0099] Where: C is the concentration of the target pollutant after the reaction; C_0 is the initial concentration of the target pollutant before the reaction; t is the photocatalytic reaction time.
[0100] In order to realize the specific use of the water-based helmet impact protection coating, a core-shell structure nanoparticle is constructed based on silicon dioxide as the core and titanium dioxide as the shell, and the characteristics of this structure are combined to enhance the self-cleaning ability and durability of the coating. A detailed embodiment is given below:
[0101] 1. Material preparation
[0102] Silica core: Silica particles with an average particle size of 50 nanometers are selected as the core. Titanium dioxide shell: Rutile titanium dioxide is selected as the shell material; other auxiliary materials.
[0103] 2. Preparation of core-shell nanoparticles
[0104] The silica particles are dispersed in a suitable solvent to form a stable suspension.
[0105] A titanium dioxide precursor is added to the suspension, and by controlling the reaction conditions (such as temperature, pH value, reaction time, etc.), titanium dioxide is uniformly deposited on the surface of silicon dioxide particles to form a core-shell structure.
[0106] The formed core-shell structured nanoparticles are washed, dried and calcined to obtain stable nanoparticles.
[0107] 3. Coating preparation and performance testing
[0108] The prepared core-shell structure nanoparticles are mixed with other coating components and stirred evenly to obtain a helmet anti-impact protective water-based coating, which is then applied to the helmet shell and subjected to necessary drying and curing treatments.
[0109] Self-cleaning ability test: Select a typical organic pollutant (such as oil stains or stains) as the target pollutant. Add a certain amount of the target pollutant to the helmet shell coated with paint, and record its initial concentration C_0. Place the helmet under simulated sunlight for a certain period of photocatalytic reaction. After the reaction is completed, measure the concentration C of the target pollutant after the reaction, and record the photocatalytic reaction time t.
[0110] The photocatalytic degradation rate constant k and the self-cleaning ability index SCI were calculated according to the above formula.
[0111] Data results: average particle size of silica core: 50 nanometers; thickness of titanium dioxide shell: 10 nanometers; BET specific surface area test results: surface area of nanoparticles per unit mass of coating is 100m / g (set value, actual value needs to be determined through experiments); mass of nanoparticles: 0.1g (mass of nanoparticles in the coating used for testing); photocatalytic reaction time: 2 hours; initial pollutant concentration C_0: 100mg / L (set value, representing the initial concentration of oil stains or stains); post-reaction pollutant concentration C: 20mg / L (set value, representing the pollutant concentration after photocatalytic reaction); Based on the above data, we can calculate:
[0112] Photocatalytic degradation rate constant k = -\frac{\ln(20 / 100)}{2} = 0.693 / hour (assuming that the pollutant concentration drops from 100 mg / L to 20 mg / L within 2 hours)
[0113] Self-cleaning ability index SCI = \frac{0.693\t imes 100}{0.1} = 693 (the larger the value, the stronger the self-cleaning ability of the coating)
[0114] Through the above examples, we have demonstrated how to use core-shell nanoparticles with silicon dioxide as the core and titanium dioxide as the shell in the water-based helmet impact protection coating to enhance the self-cleaning ability and durability of the coating. This structure combines the hardness of silicon dioxide and the photocatalytic performance of titanium dioxide, providing better protection for the helmet.
[0115] Embodiment 1
[0116] The invention discloses an anti-impact protective water-based paint for helmets, comprising the following components in parts by weight: 20 parts of epoxy resin (epoxy resin e-44, Nantong Xingchen Synthetic Materials), 20 parts of water-based polyurethane (anionic water-based polyurethane, Wanhua Chemical), 5 parts of chitosan (Shandong Chitosan Production Plant), 5 parts of polystyrene microspheres (Zhongke Keyou Nanotechnology Co., Ltd.), 3 parts of nanoclay (Sigma-Aldrich), 10 parts of acrylic resin (Xiamen Aikema Chemical Co., Ltd.), 3 parts of silicon dioxide, 2 parts of titanium dioxide (rutile type, Sichuan Longmang), 0.5 parts of defoaming agent (dimethyl silicone oil), and 0.5 parts of antifoaming agent (hydrophobic silicon dioxide).
[0117] The embodiment also provides a method for preparing a water-based helmet impact protection coating, comprising the following steps:
[0118] S1: Ultrasonic-assisted high-speed stirring technology was used, with an ultrasonic frequency of 20 kHz, a stirring speed of 1000 rpm, a mixing time of 30 minutes, and a temperature controlled at 25°C to mix the waterborne polyurethane with the chitosan solution, and to form a composite emulsion by utilizing the biocompatibility and antibacterial properties of chitosan and combining the flexibility of the waterborne polyurethane;
[0119] S2: Adopting layer-by-layer assembly technology, acrylic resin molecules were adsorbed layer by layer on the surface of nanoclay, and assembled layer by layer for 3 times. The pH value was controlled at 7 and the stirring speed was 500 rpm to construct a pre-coating emulsion with a multilayer structure.
[0120] S3: Mix the preheated epoxy resin with the diluent at 60°C for 15 minutes to reduce the viscosity, and gradually add silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed to obtain an epoxy resin base system;
[0121] S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the above mixed emulsion, and a dynamic mixer is used for mixing. The dynamic mixer has a stirring speed of 2000 rpm, a mixing time of 30 minutes, and a temperature of 30°C. The equipment can generate strong shearing and impact forces through the internal rotating elements while controlling the stirring speed, thereby ensuring that all components are completely integrated in a short time. At the same time, a defoamer and an antifoaming agent are added to reduce bubbles generated during the mixing process, and the stirring is continued until all components are completely integrated to form a uniform and stable coating system;
[0122] S5: Disperse the polystyrene microspheres for 1 hour to ensure that they are evenly dispersed. Under continuous stirring at a speed of 800 rpm, slowly add the dispersed polystyrene microspheres to the coating system in S4. Continue stirring for 30 minutes to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
[0123] Embodiment 2
[0124] The invention discloses an anti-impact protective water-based paint for helmets, comprising the following components in parts by weight: 22 parts of epoxy resin (epoxy resin e-51), 24 parts of water-based polyurethane (anionic water-based polyurethane), 7 parts of chitosan, 6 parts of polystyrene microspheres, 4 parts of nano clay, 12 parts of acrylic resin, 4 parts of silicon dioxide, 2 parts of titanium dioxide (anatase type), 0.6 parts of defoaming agent (polyether), and 0.7 parts of antifoaming agent (fatty alcohol).
[0125] The embodiment also provides a method for preparing a water-based helmet impact protection coating, comprising the following steps:
[0126] S1: Ultrasonic-assisted high-speed stirring technology was used, with an ultrasonic frequency of 25 kHz, a stirring speed of 1200 rpm, a mixing time of 40 minutes, and a temperature controlled at 30°C to mix the waterborne polyurethane with the chitosan solution, and the biocompatibility and antibacterial properties of chitosan were combined with the flexibility of the waterborne polyurethane to form a composite emulsion;
[0127] S2: Adopting layer-by-layer assembly technology, acrylic resin molecules were adsorbed layer by layer on the surface of nanoclay, and assembled layer by layer for 4 times. The pH value was controlled at 8 and the stirring speed was 700 rpm to construct a pre-coating emulsion with a multilayer structure.
[0128] S3: Mix the preheated epoxy resin with the diluent at a preheating temperature of 65° C. for 18 minutes to reduce the viscosity, and gradually add silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed to obtain an epoxy resin base system;
[0129] S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the above mixed emulsion. A dynamic mixer is used for mixing. The stirring speed of the dynamic mixer is 2500rpm, the mixing time is 40 minutes, and the temperature is controlled at 35°C. The equipment can generate strong shear force and impact force through the internal rotating element while controlling the stirring speed, thereby ensuring that all components are completely integrated in a short time. At the same time, a defoamer and an antifoaming agent are added to reduce bubbles generated during the mixing process. The stirring is continued until all components are completely integrated to form a uniform and stable coating system;
[0130] S5: Disperse the polystyrene microspheres for 1 hour to ensure that they are evenly dispersed. Under continuous stirring at a speed of 1100 rpm, slowly add the dispersed polystyrene microspheres to the coating system in S4, and continue stirring for 40 minutes to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
[0131] Embodiment 3
[0132] A water-based paint for impact protection of helmets comprises the following components in parts by weight: 26 parts of epoxy resin (epoxy resin e-44), 28 parts of water-based polyurethane (anionic water-based polyurethane), 7 parts of chitosan, 8 parts of polystyrene microspheres, 4 parts of nano clay, 14 parts of acrylic resin, 4 parts of silicon dioxide, 3 parts of titanium dioxide (rutile type), 0.8 parts of defoaming agent (dimethyl silicone oil), and 0.7 parts of antifoaming agent (hydrophobic silicon dioxide).
[0133] The embodiment also provides a method for preparing a water-based helmet impact protection coating, comprising the following steps:
[0134] S1: Ultrasonic-assisted high-speed stirring technology was used, with an ultrasonic frequency of 30 kHz, a stirring speed of 1700 rpm, a mixing time of 50 minutes, and a temperature controlled at 30°C to mix the waterborne polyurethane with the chitosan solution, and the biocompatibility and antibacterial properties of chitosan were combined with the flexibility of the waterborne polyurethane to form a composite emulsion;
[0135] S2: Adopting layer-by-layer assembly technology, acrylic resin molecules were adsorbed layer by layer on the surface of nanoclay, and assembled layer by layer for 4 times. The pH value was controlled at 8 and the stirring speed was 800 rpm to construct a pre-coating emulsion with a multilayer structure;
[0136] S3: Mix the preheated epoxy resin with the diluent at 70°C for 24 minutes to reduce the viscosity, gradually add silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed, and obtain an epoxy resin base system;
[0137] S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the above mixed emulsion, and a dynamic mixer is used for mixing. The dynamic mixer has a stirring speed of 3000 rpm, a mixing time of 50 minutes, and a temperature of 40°C. The equipment can generate strong shearing and impact forces through the internal rotating elements while controlling the stirring speed, thereby ensuring that all components are completely integrated in a short time. At the same time, a defoamer and an antifoaming agent are added to reduce bubbles generated during the mixing process, and the stirring is continued until all components are completely integrated to form a uniform and stable coating system;
[0138] S5: Disperse the polystyrene microspheres for 2 hours to ensure that they are evenly dispersed. Under continuous stirring at a speed of 1300 rpm, slowly add the dispersed polystyrene microspheres to the coating system in S4. Continue stirring for 45 minutes to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
[0139] Embodiment 4
[0140] The invention discloses an anti-impact protective water-based paint for helmets, comprising the following components in parts by weight: 30 parts of epoxy resin (epoxy resin e-51), 30 parts of water-based polyurethane (anionic water-based polyurethane), 10 parts of chitosan, 10 parts of polystyrene microspheres, 5 parts of nano clay, 15 parts of acrylic resin, 5 parts of silicon dioxide, 3 parts of titanium dioxide (titanium ore type), 1 part of defoamer (dimethyl silicone oil), and 1 part of antifoamer (fatty alcohol).
[0141] The embodiment also provides a method for preparing a water-based helmet impact protection coating, comprising the following steps:
[0142] S1: Ultrasonic-assisted high-speed stirring technology was used, with an ultrasonic frequency of 40 kHz, a stirring speed of 2000 rpm, a mixing time of 60 minutes, and a temperature controlled at 40°C to mix the waterborne polyurethane with the chitosan solution, and to form a composite emulsion by utilizing the biocompatibility and antibacterial properties of chitosan and combining the flexibility of the waterborne polyurethane;
[0143] S2: Adopting layer-by-layer assembly technology, acrylic resin molecules were adsorbed layer by layer on the surface of nanoclay, and assembled layer by layer for 5 times, with the pH value controlled at 9 and the stirring speed at 1000 rpm to construct a pre-coating emulsion with a multilayer structure;
[0144] S3: Mix the preheated epoxy resin with the diluent at 80°C for 30 minutes to reduce the viscosity, gradually add silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed, and obtain the epoxy resin base system;
[0145] S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the above mixed emulsion. A dynamic mixer is used for mixing. The stirring speed of the dynamic mixer is 4000 rpm, the mixing time is 60 minutes, and the temperature is controlled at 50°C. The equipment can generate strong shear force and impact force through the internal rotating element while controlling the stirring speed, thereby ensuring that all components are completely integrated in a short time. At the same time, a defoamer and an antifoaming agent are added to reduce bubbles generated during the mixing process. The stirring is continued until all components are completely integrated to form a uniform and stable coating system;
[0146] S5: Disperse the polystyrene microspheres for 2 hours to ensure that they are evenly dispersed. Under continuous stirring at a speed of 1500 rpm, slowly add the dispersed polystyrene microspheres to the coating system in S4, and continue stirring for 60 minutes to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
[0147] In the above-mentioned embodiments 1 to 4, in S2, the layer-by-layer assembly technical steps specifically include:
[0148] S21 Preparation of nanoclay suspension: First, disperse nanoclay in deionized water to form a stable suspension. Nanoclay has a negative charge due to the presence of hydroxyl groups or other anionic groups on its surface;
[0149] S22 Preparation of acrylic resin molecules: Select acrylic resin molecules with positive charge through chemical modification so that they can bind tightly to negatively charged nanoclay through electrostatic interaction;
[0150] S23 First layer assembly: Slowly add positively charged acrylic resin molecules into the nanoclay suspension. Due to electrostatic attraction, the acrylic resin molecules will be adsorbed on the surface of the nanoclay to form the first layer of coating;
[0151] S24 Washing and separation: After the first layer of assembly is completed, a washing step is performed by centrifugation to remove the unadsorbed acrylic resin molecules, and then the nanoclay is redispersed for the next layer of assembly.
[0152] S25 repeats the assembly process: repeats steps S23 and S24, alternately adsorbing acrylic resin molecules until a desired multilayer structure is achieved.
[0153] Comparative Example 1
[0154] A method for preparing a water-based anti-impact protective coating for a helmet is basically the same as that of the fourth embodiment, except that step S4 specifically comprises:
[0155] S41: Under controlled stirring speed, the composite emulsion and the pre-coating emulsion are first pre-mixed. The key to this step is the control of stirring speed. Variable speed stirring technology is used, and the initial stirring speed is set to 400 rpm to ensure that the two emulsions can be gently fused to avoid high-speed stirring from destroying the stability of the emulsion. As the mixing proceeds, the stirring speed is gradually increased to 900 rpm to enhance the interaction between the emulsions and promote uniform mixing, but the critical stirring speed of the emulsion stability is not exceeded;
[0156] S42: While premixing, prepare the dynamic mixer. The device is equipped with a rotating element inside, which can generate strong shear force and impact force while controlling the stirring speed. The dynamic mixer is preheated to ensure that its internal temperature is close to the temperature of the emulsion to be mixed, so as to reduce the impact of temperature differences on the mixing process;
[0157] S43: slowly adding the preheated epoxy resin base system into the dynamic mixer, and controlling the adding speed to 7% of the total amount per minute to avoid excessive local concentration and uneven mixing caused by rapid addition. While adding the epoxy resin base system, the rotating element of the dynamic mixer generates strong shear force and impact force to ensure that the epoxy resin and the premixed emulsion are completely fused in a short time.
[0158] S44: During the mixing process, bubbles may be generated due to the interaction of the components and mechanical stirring. In order to reduce the generation of bubbles, defoamers and antifoamers need to be added. When the amount of epoxy resin base system added reaches 50% of the total amount, start to slowly add defoamers and antifoamers, and the added amount is 0.5% of the total amount respectively, to ensure effective elimination and inhibition of bubble generation;
[0159] S45: During the entire mixing process, the viscosity, temperature and bubbles of the mixed system are continuously monitored. According to the monitoring results, the stirring speed and mixing time are adjusted to ensure that all components are completely integrated to form a uniform and stable coating system. The continuous stirring time is 60 minutes;
[0160] S46: When all components are completely blended and the coating system reaches the expected uniformity and stability, stop stirring and perform post-processing on the mixed coating system, such as filtering to remove possible impurities and insoluble particles, to ensure the purity of the coating and the coating effect.
[0161] Comparative Example 2
[0162] A method for preparing a helmet anti-impact protective water-based coating is basically the same as that of the fourth embodiment, except that step S5 specifically includes the following steps:
[0163] S51: Place polystyrene microspheres in a solvent containing a dispersant, such as deionized water or ethanol, with an initial concentration of 10wt%. Use a high-speed disperser for preliminary dispersion, with a dispersion speed of 3000rpm and a duration of 10 minutes to break up the agglomeration between the microspheres. Place the polystyrene microsphere suspension after preliminary dispersion in an ultrasonic processor to further promote the uniform dispersion of the microspheres using the cavitation effect of ultrasound. The ultrasonic frequency is set to 40kHz and the processing time is 20 minutes. During this period, the temperature of the suspension is maintained at 40°C to prevent overheating. Use an optical microscope or a dynamic light scattering instrument to evaluate the particle size distribution and dispersion state of the dispersed polystyrene microspheres to ensure that the microspheres achieve the desired uniform dispersion effect;
[0164] S52: Before adding the polystyrene microspheres, pre-stir the coating system obtained in step S4, and control the stirring speed at 800rpm to maintain the uniformity and stability of the coating system. Under continuous stirring, gradually add the dispersed polystyrene microsphere suspension to the coating system by slowly pumping. The addition speed is controlled at 5% of the total amount per minute to avoid uneven mixing caused by excessive local concentration. During the addition process, the viscosity, glossiness and color changes of the coating system are monitored in real time to ensure good compatibility between the polystyrene microspheres and other components of the coating system;
[0165] S53: After all the polystyrene microspheres are added, gradually increase the stirring speed to 1500rpm and continue stirring for 60 minutes to ensure that the microspheres are evenly distributed in the coating system. Evaluate the stability of the coating system after stirring, including standing and observing whether stratification, precipitation or phase separation occurs, and measuring the rheological properties of the coating by a rheometer. If the coating system has good stability, perform necessary post-processing, including filtering to remove impurities and adjusting the pH value, followed by sealed packaging to obtain the final helmet impact protection water-based coating product.
[0166] Comparative Example 1
[0167] A method for preparing an anti-impact protective water-based coating for a helmet is basically the same as that of Example 4, except that nano clay is removed and other components remain unchanged.
[0168] Comparative Example 2
[0169] A method for preparing an anti-impact protective water-based coating for a helmet is basically the same as that of Example 4, except that: in step S2, no layer-by-layer assembly is performed, and nano-clay and acrylic resin are directly mixed.
[0170] Comparative Example 3
[0171] A method for preparing an anti-impact protective water-based coating for a helmet is basically the same as that of Example 4, except that a conventional agitator is used instead of a dynamic mixer in step S4.
[0172] Comparative Example 4
[0173] A method for preparing an anti-impact protective water-based coating for a helmet is basically the same as that of Example 4, except that the polystyrene microspheres are removed and other components remain unchanged.
[0174] The water-based coatings prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were tested:
[0175] GB / T 1732-1993: Determination of impact resistance of paint films. This standard is used to determine the impact resistance of paint films under high-speed gravity.
[0176] GB / T 9286-1998: Cross-cut test for paint and varnish films. This standard is used to evaluate the adhesion of coatings to substrates.
[0177] GB / T 1771-2007: Determination of neutral salt spray resistance of paints and varnishes. This standard is used to test the corrosion resistance of coatings in salt spray environments.
[0178] GB / T 5210-2006: Pull-off adhesion test for paints and varnishes. This method is used to determine the pull-off adhesion between a coating and a substrate or between two coatings.
[0179] Specific detection method
[0180] Impact resistance test: According to GB / T 1732-1993 standard, use a paint film impactor to impact the coating and observe whether the coating has cracking, peeling, etc.
[0181] Cross-cut test: According to GB / T 9286-1998, a grid of a certain size is scratched on the coating surface, then the surface is taped and quickly torn off to observe the peeling of the coating inside the grid.
[0182] Salt spray test: According to GB / T 1771-2007, the painted specimens are placed in a salt spray test chamber to simulate the marine or industrial salt spray environment to test the corrosion resistance of the coating.
[0183] Pull-off adhesion test: According to GB / T 5210-2006, a tensile testing machine is used to measure the adhesion between the coating and the substrate.
[0184] The results are shown in Table 1:
[0185] Table 1
[0186]
[0187]
[0188] From Table 1 above, it can be directly obtained that with the adjustment of the proportion of each component and the optimization of the preparation process, the impact resistance of the coating shows a trend of gradual enhancement. Example 4 shows the best impact resistance, which is related to the synergistic effect between the components and the uniform and stable coating system formed during the preparation process.
[0189] All examples reached the 0-level standard in the cross-cut test, that is, there was no peeling phenomenon. This shows that the adhesion between the coating prepared in each example and the substrate is very strong, and the coating can remain intact and is not easy to fall off when subjected to the cross-cut test.
[0190] All examples can withstand 1000 hours in the salt spray test without corrosion, which shows that the coatings prepared in each example have good corrosion resistance and can maintain the integrity and functionality of the coating in a harsh salt spray environment.
[0191] Pull-off adhesion: From the comparison of pull-off adhesion, it can be seen that with the optimization of the preparation process and the adjustment of the proportion of each component, the adhesion of the coating is gradually enhanced. Example 3 and Example 4 show the best adhesion performance.
[0192] In summary, the coatings prepared in all examples showed good impact resistance, adhesion and corrosion resistance. With the adjustment of the proportion of each component and the optimization of the preparation process (such as ultrasonic frequency, stirring speed, mixing time, etc.), the various properties of the coating showed a trend of gradual enhancement.
[0193] Comparative Example 1 achieved higher impact resistance of 62 kg·cm by optimizing the mixing process in step S4. This shows that more sophisticated mixing process control, including the use of variable speed stirring and dynamic mixers, can help improve the impact resistance of coatings. Comparative Example 2 further improved the dispersion and addition of polystyrene microspheres in step S5, thereby achieving higher impact resistance of 65 kg·cm. This shows that uniform dispersion of polystyrene microspheres and good compatibility with the coating system are crucial to improving impact resistance.
[0194] All the examples and control examples reached the 0-level standard in the cross-cut test, that is, there was no peeling phenomenon. This shows that the adhesion between the coating obtained by each preparation process and the substrate is very strong, and the coating can remain intact when subjected to the cross-cut test.
[0195] Salt spray test: Example 4 can withstand 1000 hours without corrosion in the salt spray test. Both Control Example 1 and Control Example 2 show better corrosion resistance and can withstand 1100 hours without corrosion. This shows that by optimizing the mixing and dispersion process, not only the physical properties of the coating (such as impact resistance) are improved, but also its chemical stability is enhanced, so that it has a longer service life in harsh environments.
[0196] Pull-off adhesion: The pull-off adhesion of Example 4 is 6.3 MPa, showing strong adhesion. The adhesion of Control Example 1 is improved to 7.1 MPa by improving the mixing step. This once again proves the importance of a fine mixing process for enhancing the bonding between the coating and the substrate. Control Example 2 further improves the adhesion to 7.5 MPa by optimizing the dispersion and addition process of polystyrene microspheres. This shows that the uniform distribution and good compatibility of microspheres in the coating system have a significant effect on improving adhesion.
[0197] Reference Figure 1-5 , in Example 4 and Comparative Example where other conditions are the same:
[0198] Impact resistance:
[0199] The impact resistance of Example 4 is 55kg·cm, showing good impact resistance. The impact resistance of Comparative Example 1 (removing nanoclay) drops significantly to 40kg·cm, indicating that nanoclay plays an important role in enhancing the impact resistance of the coating. The impact resistance of Comparative Example 2 (no layer-by-layer assembly) is 45kg·cm, which is lower than that of Example 4, indicating that the layer-by-layer assembly technology helps to improve the impact resistance of the coating. The impact resistance of Comparative Example 3 (without using a dynamic mixer) is 48kg·cm, slightly lower than that of Example 4, indicating that the use of a dynamic mixer has a positive effect on improving the performance of the coating. The impact resistance of Comparative Example 4 (removing polystyrene microspheres) is the lowest, at 35kg·cm, indicating that polystyrene microspheres are essential for enhancing the impact resistance of the coating.
[0200] Cross-cut test:
[0201] Both Example 4 and Comparative Example 3 reached the Grade 0 standard, indicating that the adhesion between the coating and the substrate is very strong. The cross-hatch test grades of Comparative Examples 1 and 4 are relatively high, at Grade 3 and Grade 2, respectively, indicating that the removal of nanoclay or polystyrene microspheres will significantly reduce the adhesion of the coating. Comparative Example 2 is Grade 1, indicating that not performing layer-by-layer assembly will also affect the adhesion of the coating, but the impact is relatively small.
[0202] Salt spray test:
[0203] Example 4 and Comparative Example 3 both showed excellent corrosion resistance in the salt spray test and could withstand 1000 hours without corrosion. Comparative Examples 1, 2, and 4 had poor corrosion resistance and were corroded at 700 hours, 850 hours, and 650 hours, respectively, indicating that nanoclay, layer-by-layer assembly technology, and polystyrene microspheres all play an important role in improving the corrosion resistance of the coating.
[0204] Pull-off adhesion:
[0205] The pull-off adhesion of Example 4 is 6.3 MPa, showing strong adhesion. The adhesion of Comparative Examples 1, 2, 3, and 4 is lower than that of Example 4, among which Comparative Example 4 is the lowest (3.0 MPa), which once again proves the important influence of each component and preparation process on the performance of the coating.
[0206] In the present invention, through the synergistic effect of various components, especially the energy absorption and self-repairing functions of polystyrene microspheres, and the interpenetrating polymer network constructed by chitosan and waterborne polyurethane, the coating can effectively resist external impact and protect the internal structure of the helmet from damage.
[0207] The photocatalytic properties of titanium dioxide nanoparticles are combined with the hardness of silicon dioxide to construct core-shell structured nanoparticles that can enhance the self-cleaning ability of the coating, reduce the adhesion of pollutants, and maintain the cleanliness of the coating surface.
[0208] The dense pre-coating layer formed by nanoclay and acrylic resin improves the adhesion and durability of the coating. At the same time, the stability of the coating is guaranteed by the sophisticated preparation process and component selection, and it can maintain good performance in long-term use.
[0209] The elastomeric properties of polystyrene microspheres combined with the flexibility and abrasion resistance of chitosan and waterborne polyurethane create a coating system that absorbs and disperses impact energy. This synergistic effect significantly improves the coating's impact resistance and provides more effective protection for the helmet.
[0210] The introduction of nanomaterials such as nanoclay, silica and titanium dioxide not only enhances the hardness and wear resistance of the coating, but also synergistically improves the self-cleaning ability and antibacterial function of the coating through their special physical and chemical properties (such as photocatalytic activity).
[0211] In summary, the energy absorption and self-repairing functions of the polystyrene microspheres of the present invention cooperate with the biocompatibility and antibacterial function of chitosan, as well as the flexibility and wear resistance of waterborne polyurethane, to jointly build a powerful protection system; the pre-coating structure of nanoclay and acrylic resin enhances the adhesion and stability of the coating; and the core-shell structure nanoparticles of silicon dioxide and titanium dioxide give the coating excellent self-cleaning ability. The synergy between these components not only improves the overall performance of the coating, but also makes it more adaptable to complex and changeable use environments, providing all-round protection for the helmet.
[0212] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-based paint for helmet impact protection, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of epoxy resin, 20-30 parts of waterborne polyurethane, 5-10 parts of chitosan, 5-10 parts of polystyrene microspheres, 3-5 parts of nano clay, 10-15 parts of acrylic resin, 3-5 parts of silicon dioxide, 2-3 parts of titanium dioxide, 0.5-1 part of defoaming agent and 0.5-1 part of antifoaming agent.
2. The water-based helmet impact protection coating according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 23 parts of epoxy resin, 26 parts of waterborne polyurethane, 7 parts of chitosan, 8 parts of polystyrene microspheres, 4 parts of nano clay, 12 parts of acrylic resin, 4 parts of silicon dioxide, 2 parts of titanium dioxide, 0.8 parts of defoaming agent and 0.7 parts of antifoaming agent.
3. The water-based helmet impact protection coating according to claim 1, characterized in that: The epoxy resin is one of epoxy resin e-44 and epoxy resin e-51, and the viscosity of the epoxy resin is 1000-1500 mPa·s; the waterborne polyurethane adopts anionic waterborne polyurethane, and the average particle size is 50-100 nanometers; the molecular weight of the chitosan is 100,000-300,000; the average particle size of the polystyrene microspheres is 1-5 micrometers; the glass transition temperature of the acrylic resin is 30-50°C, and the weight average molecular weight is 50,000-100,000; the crystal form of the titanium dioxide is one of rutile type or anatase type, and the average particle size is 0.2-0.4 micrometer; the defoamer is one of dimethyl silicone oil and polyether; the antifoaming agent is one of hydrophobic silica and fatty alcohol.
4. A helmet anti-impact protective water-based paint according to claim 1 or 2, characterized in that: The chitosan and the waterborne polyurethane construct an interpenetrating polymer network, wherein the chitosan network provides biocompatibility and antibacterial functions, and the waterborne polyurethane network contributes to flexibility and wear resistance; The polystyrene microspheres are elastomers with a deformable core, which is composed of a cross-linked polymer network and can change shape and absorb energy under the action of external forces. The surface of the polystyrene microspheres is covered with a nanoscale self-healing layer, which can quickly self-repair when the microspheres are broken to maintain the integrity of the coating.
5. The water-based helmet impact protection coating according to claim 1 or 2, characterized in that: The chitosan is modified, and a functional group capable of chelating calcium ions is introduced into the molecular chain of the chitosan; The acrylic resin is a copolymer with a core-shell structure, the core layer is a hard segment, and the shell layer is a soft segment; The waterborne polyurethane has a star-shaped structure, the central core is a rigid aromatic structure, and the periphery is a flexible aliphatic chain segment; The surface of the titanium dioxide nanoparticles is modified with a metal oxide film having photocatalytic activity by atomic layer deposition technology and designed into a nano-shaped structure, wherein the nano-shaped structure includes nano-flowers, nano-trees or nano-stars; The interior of the polystyrene microspheres is a core-shell structure with a gradient density distribution, and / or the surface of the polystyrene microspheres is modified with nano-scale silicon dioxide particles.
6. The water-based helmet impact protection coating according to claim 1 or 2, characterized in that: The core-shell structure nanoparticles are constructed with the silicon dioxide as the core and the titanium dioxide as the shell. This structure can combine the hardness of silicon dioxide and the photocatalytic performance of titanium dioxide to enhance the self-cleaning ability of the coating. The self-cleaning ability index is set as SCI, then: SCI=\frac{k\timesA surface }{M particle } Where: k is the photocatalytic degradation rate constant; A surface is the surface area of nanoparticles per unit mass of coating, obtained by BET specific surface area test; M particle is the mass of the nanoparticle; k=-\frac{\ln(C / C_0)}{t} Where: C is the concentration of the target pollutant after the reaction; C_0 is the initial concentration of the target pollutant before the reaction; t is the photocatalytic reaction time.
7. A method for preparing the water-based helmet impact protection coating according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: Using ultrasonic-assisted high-speed stirring technology, water-based polyurethane and chitosan solution are mixed to form a composite emulsion; S2: dispersing nanoclay in deionized water to form a stable suspension, and slowly adding acrylic resin under stirring to form a dense pre-coating emulsion; S3: mixing the preheated epoxy resin with a diluent to reduce the viscosity, gradually adding silicon dioxide and titanium dioxide to ensure that the components are evenly dispersed to obtain an epoxy resin base system; S4: The composite emulsion and the pre-coating emulsion are mixed at a controlled stirring speed to avoid destroying the stability of the emulsion, and the epoxy resin base system is slowly added to the mixed emulsion, and a defoamer and an antifoaming agent are added at the same time, and the stirring is continued until all components are completely blended to form a uniform and stable coating system; S5: The polystyrene microspheres are dispersed, and then slowly added into the coating system in S4 under continuous stirring, and stirring is continued for a period of time to ensure that the polystyrene microspheres are evenly distributed in the coating to obtain a helmet anti-impact protective water-based coating.
8. The method for preparing a water-based helmet impact protection coating according to claim 7, characterized in that: In S2, a layer-by-layer assembly technique is used to adsorb acrylic resin molecules layer by layer on the surface of the nanoclay to construct a pre-coating emulsion with a multi-layer structure.
9. The method for preparing a water-based helmet impact protection coating according to claim 7, characterized in that: The S4 specifically includes: S41: Under controlled stirring speed, the composite emulsion and the pre-coating emulsion are first pre-mixed, and a variable speed stirring technology is used, the initial stirring speed is set to 400 rpm, and the stirring speed is gradually increased to 900 rpm; S42: while premixing, preparing a dynamic mixer, which has a rotating element inside and can generate strong shear force and impact force while controlling the stirring speed, and preheating the dynamic mixer to reduce the influence of temperature difference on the mixing process; S43: slowly adding the preheated epoxy resin base system into the dynamic mixer, and while adding the epoxy resin base system, a strong shear force and impact force are generated by the rotating element of the dynamic mixer; S44: During the mixing process, when the amount of epoxy resin base system added reaches 50% of the total amount, the defoamer and the antifoam agent are slowly added; S45: During the entire mixing process, the viscosity, temperature and bubble conditions of the mixed system are continuously monitored, and the continuous stirring time is adjusted according to the monitoring results; S46: When all components are completely blended, stop stirring and perform post-processing on the mixed coating system to ensure the purity and coating effect of the coating.
10. The method for preparing a water-based helmet impact protection coating according to claim 7, characterized in that: The S5 specifically includes the following steps: S51: placing polystyrene microspheres in a solvent containing a dispersant, using a high-speed disperser for preliminary dispersion, placing the polystyrene microsphere suspension after preliminary dispersion in an ultrasonic processor, and using an optical microscope to evaluate the particle size distribution and dispersion state of the dispersed polystyrene microspheres to ensure that the microspheres achieve the desired uniform dispersion effect; S52: before adding the polystyrene microspheres, pre-stirring the coating system obtained in step S4, and gradually adding the dispersed polystyrene microsphere suspension into the coating system by slowly pumping under continuous stirring; S53: After all the polystyrene microspheres are added, gradually increase the stirring speed and evaluate the stability of the coating system after stirring, including standing and observing whether stratification, precipitation or phase separation occurs, and measuring the rheological properties of the coating by a rheometer. If the stability of the coating system is good, post-processing is carried out, followed by sealed packaging to obtain the final helmet impact protection water-based coating product.
Citation Information
Patent Citations
Water-based coating containing graphene / zinc-aluminum hydrotalcite nano composition and preparation method thereof
CN106995643A
Anticorrosive and antibacterial waterborne coating
CN107858028A
Water-soluble silicon steel sheet paint and preparation process thereof
CN111253826A
Preparation method of good-weather-resistance self-repairing composite coating for invisible car cover
CN114874682A